PENGARUH KEMAMPUAN LITERASI DIGITAL DAN KEDISIPLINAN SISWA TERHADAP HASIL BELAJAR SISWA KELAS XI BISNIS DIGITAL SMK SWASTA BUDI AGUNG MEDAN T.A 2024/2025 - Sulaiman Falah Siregar; Dita Eka Pertiwi Sirait (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this study was to determine and analyze the influence of digital literacy skills and student discipline on the learning outcomes of Grade XI Digital Business students in the 2024/2025 academic year. This research employed a quantitative method with an ex post facto approach. Data were collected through observation, documentation, and questionnaires administered to 30 respondents, then analyzed using multiple linear regression with the assistance of SPSS 25. The results showed that both digital literacy skills and student discipline had a positive and significant effect, both partially and simultaneously, on student learning outcomes. The coefficient of determination (R²) value was 0.596, indicating that these two variables contributed 59.6% to the students’ learning outcomes.